Standards of Judicial Conduct – Ethical Aspects: Seminar Ankara, Turkey September 24, 2004 - (:unkn) unknown (My University, 2016)
A cornerstone of a constitutional state and a society governed by the rule of law isthe separation of powers as postulated by the philosophers Charles de Montesquieuand Immanuel Kant. The assignment of the three main duties of the state authority –i.e. legislature, executive and judiciary – to three different independent from eachother organs of the state is an essential in democratic societies.